Bridging Theory and Practice: Project-Based Learning in EFL Classrooms - Neupane, Ram Nath (Kanya Journal, 2025)
Project-Based Learning (PBL) is a learner-centred approach that develops learner autonomy, collaboration, and active participation in the learning process. It leads the students to overcome real-world problems through individual learning styles, strengths, and capacities. The present study aims to explore the classroom implementation of project-based learning in EFL classrooms. To achieve this, five English language teachers from two constituent campuses of Tribhuvan University were purposively selected and semi-structured interviews were conducted using an interview guideline to gather the intended information. The collected data were analyzed under different themes based on their responses. The findings reveal that teachers emphasize the teaching importance of PBL in developing learner-centered teaching, enhancing critical thinking, and encouraging integration of four language skills in authentic contexts. However, they also reported various challenges, such as time constraints, large classrooms, and limited training that hinder adoption of PBL. Addressing such issues can promote learner autonomy, engagement, and meaningful learning outcomes. The study recommends sufficient teacher training, curriculum reform, policy design, evaluation rethink, and strong institutional support to make the PBL more effective in EFL context.